If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 = -6(n + -8) Reorder the terms: 12 = -6(-8 + n) 12 = (-8 * -6 + n * -6) 12 = (48 + -6n) Solving 12 = 48 + -6n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '6n' to each side of the equation. 12 + 6n = 48 + -6n + 6n Combine like terms: -6n + 6n = 0 12 + 6n = 48 + 0 12 + 6n = 48 Add '-12' to each side of the equation. 12 + -12 + 6n = 48 + -12 Combine like terms: 12 + -12 = 0 0 + 6n = 48 + -12 6n = 48 + -12 Combine like terms: 48 + -12 = 36 6n = 36 Divide each side by '6'. n = 6 Simplifying n = 6
| 1/4+4x/5=12/20 | | 7(8v+7)+5(6v-8)=245 | | (X^2)-8x+137=0 | | -4y-7=3y-8 | | y+2x+60=180 | | 4/2+6t=2 | | 5/4-3/16 | | 4x-16=3x-7 | | 4y-10=3x | | 7/x+2-6=5x+14/x+2 | | -2(2+3)=2(5t-3) | | x-0.15x=55 | | 0.6666666666d+1=16-d | | 6x-4x-3=5 | | 264+26=528 | | 3x+20/4+x+38/7=14 | | x+5=5x+2 | | 2(7w+2)-4(w-7)=72 | | -4x+9=59 | | f+4overg=6 | | m/10-4=16 | | 7x+2(4x+7)=149 | | 2x+3+x=9 | | 5g+3(-5+4g)=1-g | | 2/3a+1/4 | | 2(7w+2)+4(w-7)=72 | | 15x-3=4x+15 | | 1/7=4/7-1/5k | | 11/4-3/16 | | 6/15=x-2/40 | | 4-6x=7x-87 | | t/t-8+4=8/t-8 |